An online windowed fourier transformer for fringe pattern analysis = a windowed fourier transform applet - Ngiam, Vincent Tee Wee. (2012)
To build a Java applet equivalent of an already available Matlab program which processed and analysed fringe pattern block by block using Windowed Fourier Transform technique that involved two algorithms, Windowed Fourier Filtering and Windowed Fourier Ridges.